The effects of the 2004 tsunami on a coastal aquifer in Sri Lanka - Vithanage, Meththika; Engesgaard, P.; Villholth, Karen G.; Jensen, K.H. (Wiley, 2012)
On December 26, 2004, the earthquake off the southern coast of Sumatra in the Indian Ocean generated far-reaching tsunami waves, resulting in severe disruption of the coastal aquifers in many countries of the region. The objective of this study was to examine the impact of the tsunami on groundwater in coastal areas. Field investigations on the east coast of Sri Lanka were carried out along a transect located perpendicular to the coastline on a 2.4 km wide sand stretch bounded by the sea and a lagoon. Measurements of groundwater table elevation and electrical conductivity (EC) of the groundwater were carried out monthly from October 2005 to August 2007. The aquifer system and tsunami saltwater intrusion were modeled using the variable-density flow and solute transport code HST3D to understand the tsunami plume behavior and estimate the aquifer recovery time. EC values reduced as a result of the monsoonal rainfall following the tsunami with a decline in reduction rate during the dry season. The upper part of the saturated zone (down to 2.5 m) returned to freshwater conditions (EC < 1000 ?S/cm) 1 to 1.5 years after the tsunami, according to field observations. On the basis of model simulations, it may take more than 15 years for the entire aquifer (down to 28 m) to recover completely, although the top 6 m of the aquifer may become fresh in about 5 years.